Analisis Psikologis Dalam Mengedukasi Remaja Pecinta Tedong Silaga Di Toraja (International Forum of Researchers and Lecturers, 2023)
The activity of fighting ma'pasilaga tedong (buffalo fighting) is one of the Toraja culture which is favored by many people, one of them is teenagers. The euphoria of teenagers towards buffalo fighting activities is very high. Adolescents' penchant for buffalo fighting activities will be seen how the impact occurs on adolescents, especially in the formation of traits or character in the future. To see this, the author uses the observation method by observing the activities of adolescents in buffalo fighting activities and the library method through books and journals. In particular, the author uses the theory of Behaviorism, social cognitive, and ecology. From this it can be concluded that buffalo fighting activities are a determining factor in the formation of character and traits, especially for teenagers who are involved in them, especially for teenagers who have euphoria about buffalo fighting. Therefore education is needed from various parties such as family and social environment.